Evaluation of thoracic impedance trends for implant-based remote monitoring in heart failure patients - Results from the (J-)HomeCARE-II Study - Maier, Sebastian K.G.; Paule, Stefan; Jung, Werner; Koller, Marcus; Ventura, Rodolfo; Quesada, Aurelio; Bordachar, Pierre; García-Fernández, F. Javier; Schumacher, Burghard; Lobitz, Nicole; Takizawa, Kaname; Ando, Kenji; et al. (Journal of Electrocardiology, 2019)
Remote monitoring by implantable devices substantially improves management of heart failure (HF) patients by providing diagnostic day-to-day data. The use of thoracic impedance (TI) as a surrogate measure of fluid accumulation is still strongly debated. The multicenter HomeCARE-II study evaluated clinically apparent HF events in the context of remote device diagnostics, focusing on the controversial role of TI. We followed 497 patients (66.6 ± 10.1 years, 77% male, QRS 139.8 ± 36.0 ms, ejection fraction 26.8 ± 7.0%) implanted with a CRT-D (67%) or an ICD (33%) for 21.4 ± 8.1 months. An independent event committee confirmed 171 HF events of which 82 were used to develop a TI-based algorithm for the prediction of imminent cardiac decompensation. Highly inter-individual variations in patterns of TI trends were observed. The algorithm resulted in a sensitivity of 41.5% (50.0%) with 0.95 (1.34) false alerts per patient year, and a positive predictive value of 7.9% overall and 27.9% in the HF event group of patients. Averaged ratio statistics showed a significant pre-hospital decrease and a highly significant in-hospital increase in TI after intensified diuresis. Recurrent decompensations turned out to be preceded by a significantly stronger decrease of TI compared to first events with a higher chance for detection (63.6% sensitivity, p < 0.05). Overall performance in predicting imminent decompensation by monitoring TI alone is limited due to its high inter-patient variability. TI stand-alone applications should be redirected towards a target population with more advanced symptoms where post-hospital observation aimed to maintain the patient's discharge status might be the most valuable approach. ClinicalTrials.gov Identifier NCT00711360 (HomeCARE-II) and NCT01221649 (J-HomeCARE-II). •Thoracic impedance (TI) is a variable for heart failure monitoring due to its significant pre-hospital and in-hospital changes.•Recurrent decompensations are preceded by a significantly larger pre-hospital decrease and are therefore more likely to be detected.•Overall performance in predicting decompensation by sole observation of TI is clearly limited.•Post-hospital observation of TI might be the most promising application to avoid recurrent decompensation.